COMMUNITY-BASED DEVELOPMENT OF THE BELITUNG GEOPARK IN THE MANAGEMENT OF GEOTOURISM AREAS IN EAST BELITUNG REGENCY, INDONESIA - C Christianingrum; Irvani Irvani; Nur Ahmad Ricky Rudianto; Askarov Abror Sobirovich (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the development of Geopark Belitung as a geotourism area based on community participation in East Belitung Regency, Indonesia. The research aims to analyze the physical conditions of geosites, the forms and levels of community participation, and the management strategies applied in developing community-based geotourism. A qualitative descriptive approach was employed, using purposive sampling to select key informants from local communities, geopark managers, and government institutions. Data were collected through in-depth interviews, field observations, and document analysis, and analyzed using an interactive model of data reduction, data display, and conclusion drawing. The findings reveal that Geopark Belitung possesses significant geological, ecological, and cultural potential; however, the level of development and supporting facilities remains uneven across geosites. Community participation is largely limited to operational and economic activities, while involvement in planning, decision-making, and evaluation processes is still minimal. The absence of systematic capacity-building programs, institutional strengthening, and sustained external support constrains the effectiveness of community-based geotourism development. This study highlights the need for more inclusive and collaborative governance models that integrate community empowerment, conservation awareness, and sustainable destination management to enhance the long-term competitiveness and sustainability of Geopark Belitung.